Frustrated pretransitional phenomena in aperiodic composites - Mariette, C.; Frantsuzov, Ilya; Wang, Bo; Guerin, L.; Rabiller, P.; Hollingsworth, Mark D.; Toudic, B. (My University, 2016)
This paper reports on symmetry breaking in the aperiodic inclusion compound n-octadecane/urea and its isotopomer n-octadecane/urea-d(4). The high-symmetry phase is described by a hexagonal rank-4 superspace group. Pretransitional phenomena in this crystallographic superspace reveal competing short-range-ordering phenomena within the high-symmetry phase. Very high-resolution diffraction data show that critical scattering appears at inequivalent points within the four-dimensional Brillouin zone, although the first phase transition at T-c1 near 158 K implies the condensation at only one of those points. The resulting superspace group remains of dimension 4. Two other phase transitions are reported at T-c2 = 152.8(4) K and T-c3 = 109(4) K in n-octadecane/urea-d(4). The two low-symmetry phases that arise are described by rank-5 superspace groups.
Citation: Mariette, C., Frantsuzov, I., Wang, B., Guerin, L., Rabiller, P., Hollingsworth, M. D., & Toudic, B. (2016). Frustrated pretransitional phenomena in aperiodic composites. Physical Review B, 94(18), 9. doi:10.1103/PhysRevB.94.184105
Keywords: Urea Inclusion-Compounds; X-Ray-Diffraction; Diffuse-Scattering; Phase-Transition; N-Paraffins; Compounds Oc(Nh2)2+Cnh2N+2